PEMANFAATAN LIMBAH KRUSTASEA DALAM PEMBUATAN GLUKOSAMIN HIDROKLORIDA DENGAN METODE AUTOKLAF - Pipih Suptija; Bustami Ibrahim; Ernawati Ernawati (Jurnal Teknologi Perikanan dan Kelautan, 2014)
Utilization of crustacean shell waste to produce chitosan can continue by derivatisation to produced glucosamine. GlcN HCl is one of the nutraceuticals product widely consumed for reducing osteoarthritis symptoms. The minimum local production of glucosamine itself encourages a proper glucosamine production technology. The purpose of this study was to obtain optimum production technique of glucosamine hydrochloride. Production of glucosamine hydrochloride used presured hydrolysis method by pressured treatment (autoclaving), heating time (hours), and acid (% v/v). Characteristic of glucosamine hydrochloride was determined for solubility parameters, appearance, yields, value loss on drying (LOD), the melting point temperature and FTIR absorption. The quality standard of hydrolyzed glucosamine refers to the standard of United State Pharmacopeia. The results showed that the optimum techniques of glucosamine hydrochloride production were using HCl (8%) (v/v) and 1 atm pressure for 1 hour. Hydrolyzedglucosamine hydrochloride was completely dissolved in water, yellowish-white powder appearance with (69.80%) of yield, LOD value was 0.92%, and the melting point temperature was 190-193 Â°C. FTIR spectrum showed functional group of OH at 300-3263 cm-1 and amida group at 1566 cm-1, wassimilar absorption band patterns with hydrolyzed glucosamine hydrochloride of standard.